2018
DOI: 10.1088/1475-7516/2018/10/011
|View full text |Cite
|
Sign up to set email alerts
|

A novel probe of ionized bubble shape and size statistics of the epoch of reionization using the contour Minkowski Tensor

Abstract: We employ the rank-2 contour Minkowski Tensor in two dimensions to probe length and time scales of ionized bubbles during the epoch of reionization. We demonstrate that the eigenvalues of this tensor provide excellent probes of the distribution of the sizes of ionized bubbles, and from it the characteristic bubble sizes, at different redshifts. We show that ionized bubbles are not circular, and hence not spherical in three dimensions, as is often assumed for simplified analytic arguments. We quantify their sha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 64 publications
(114 reference statements)
1
40
0
Order By: Relevance
“…To characterize the magnetic structures, we use the Minkowski functionals [76]. Minkowski functionals have been used in studying morphology of structures in a number of numerical simulations [34,[77][78][79][80][81][82] and observations [83][84][85][86]. The morphology of a d-dimensional structure can be described by d + 1 Minkowski functionals.…”
Section: Morphology Of Magnetic Structuresmentioning
confidence: 99%
“…To characterize the magnetic structures, we use the Minkowski functionals [76]. Minkowski functionals have been used in studying morphology of structures in a number of numerical simulations [34,[77][78][79][80][81][82] and observations [83][84][85][86]. The morphology of a d-dimensional structure can be described by d + 1 Minkowski functionals.…”
Section: Morphology Of Magnetic Structuresmentioning
confidence: 99%
“…Only weak upper limits on the EoR 21-cm PS have been estimated till date (McGreer, Mesinger & Fan 2011;Parsons et al 2014;Pober, Greig & Mesinger 2016a). In addition to the PS, various other statistics such as the variance (Patil et al 2014), bispectrum (Yoshiura et al 2015;Shimabukuro et al 2017;Majumdar et al 2018), and the Minkowski Functional (Bag et al 2018;Kapahtia et al 2018) have been proposed to quantify the EoR 21-cm signal .…”
mentioning
confidence: 99%
“…Therefore, their values can be important characteristic features that can discriminate different models. Note that in [44] it was found that at z 0.5 , N con = N hole . We will show this to be true for all models we have considered in our study.…”
Section: Morphology Of Density Field: δ Nlmentioning
confidence: 93%
“…5). For this choice of ν cut , N con ∼ N hole at x HI = 0.5 [44]. For the x HI field, a connected region corresponds to a neutral region and a hole corresponds to an ionized region.…”
Section: Morphology Of Density Field: δ Nlmentioning
confidence: 98%
See 1 more Smart Citation